PERCEPTIONS OF VIOLENCE IN A FAMILY HEALTH UNIT SETTING - Maria de Lourdes Denardin Budó; Maria Denise Schimith; Dalva Cezar Silva; Silvana de Oliveira Silva; Pâmela Batista de Almeida (Universidade Federal do Paraná, 2012)
The objective was to learn about the context of violence in the setting of a Family Health Unit in the south of Brazil, through qualitative research carried out in 2008. Participatory rapid appraisal was used for data collection. Nineteen key participants were involved, these being six community leaders, six community health assistants, and seven other members of the health team. The data was submitted to thematic content analysis, which produced three categories: policing as a factor for security; violence influenced by social context; and the banalization of violence. The results reveal a complex understanding of violence although its banalization may be verified. Nursing, along with the health team, can contribute to the reduction of levels of violence, putting itself in the position of mediator in the construction of a social network which identifies, incorporates, articulates and promotes actions which are capable of improving the life of the community